Bagaimana Kelelahan Emosional Mempengaruhi Komitmen Serta Dampaknya Terhadap Kinerja Pegawai Kesehatan di Masa Pasca Pandemi Covid-19 - Leni Gustina; Tonny Yuwanda; Shinta Bella (Kuras Institute, 2022)
Health workers are one of the human resources who have been heavily affected by the post-COVID-19 pandemic. In addition to physical health, emotional fatigue is also obtained by health workers. This study aims to examine the effect of leader member exchange, emotional exhaustion and the mediating role of organizational commitment on the performance of health workers. The sample selection technique used random sampling and obtained a sample of 59 respondents from health workers at Alahan Panjang Public Health Center, Solok. The data analysis technique used Structure Equation Model (SEM) - Partial Least Square (PLS). From the results of the study it can be concluded that LMX has no significant effect on emotional exhaustion, but LMX has a significant effect on organizational commitment. Emotional exhaustion has a significant effect on organizational commitment and emotional exhaustion also has a significant effect on employee performance and organizational commitment has a significant effect on performance. The mediating role of organizational commitment between emotional exhaustion and performance has a negative and insignificant effect.